The Effect of Digital Addiction Training on University Students’ Digital Addiction, Sleep Quality, and Orexin-A Levels: Randomized Controlled Trial - Zehra İncedal Sonkaya; Burak Yazgan (BMC Psychology)
Abstract Background Digital addiction negatively impacts brain functions and behaviors, particularly in this era of increasing reliance on the online world. It disrupts the sleep-wake cycle and contributes to insomnia. Orexins, also known as hypocretins, are peptides produced by neuronal cells in the brain. Additionally, orexin-A levels have been associated with insomnia, REM-sleep behavior disorder, anxiety, and cognitive dysfunction. However, despite the potential link between orexin-A levels, digital addiction, and sleep quality, studies on this topic remain limited. Objective This study aimed to provide digital addiction training to university students, a population where digital addiction is more prevalent, and to investigate the effects of this training on their digital addiction levels, sleep quality, and orexin-A peptide levels. Methods This research was designed as a pre-test-post-test experimental study with a control group. Based on power analysis, a total of 42 students were included in the study, with 21 participants in the intervention group and 21 participants in the control group. Data were collected using a sociodemographic questionnaire, Digital Addiction Scale, and Pittsburgh Sleep Quality Index (PUKI). Blood samples were collected from students assigned to the intervention and control groups both before the training and to measure orexin-A levels. The intervention group then participated in four sessions of combating digital addiction training. Upon completion of the training program, both the intervention and control groups underwent a post-test, and their orexin-A levels were remeasured. In the analysis of data, independent sample t-test, one-way analysis of covariance (ANCOVA), Spearman and Pearson’s correlation tests were used for correlation analyses. In all statistical analyses, Type I error margin was set as p <.05. Results Intervention group students showed significant changes in the Pittsburgh Sleep Quality Index (t (19) = 6.28, p <.001, d = 1.40), Digital Addiction total (t (19) = 8.11, p <.001, d = 1.81) and its sub-subscales of Overuse (t (19) = 6.35, p <.001, d = 1.42), Non-restraint (t (19) = 5.07, p <.001, d = 1.13), Emotional State (t (19) = 4.17, p <.001, d = 0.93), and Dependence (t (19) = 3.85, p <.01, d = 0.86) scores. All observed differences demonstrated a high effect size. However, no significant changes were observed in orexin-A levels between the control and intervention groups, nor were there time-dependent changes (before and after the intervention) within the intervention group. Furthermore, no significant correlation was found between orexin-A levels and both the Digital Addiction Score and the Pittsburgh Sleep Quality Index scores. Conclusion Digital addiction training has been shown to be an effective program in reducing students’ levels of overuse, non-restraint, emotional state, dependence, and overall digital addiction. Trial registration Clinical Trials NCT06738524. Date of registration 17.12.2024 (Retrospectively registered).